Marketing and managing tourism destinations - Morrison, Alastair M. (Routledge, 2024)
"Marketing and Managing Tourism Destinations is a comprehensive and integrated introductory textbook covering destination management and marketing in one volume. It focuses on how destination management is planned, implemented, and evaluated as well as the management and operations of destination management organizations (DMOs), how they conduct business, major opportunities, and challenges and issues they face to compete for the global leisure and business travel markets. Written by an author with many years of industry practice, university teaching and professional training experience, this book is the essential guide to the subject for tourism, hospitality, and events students and industry practitioners alike"